Stratigraphy, isotope geochemistry, seismic stratigraphy and paleogeography of the Lagoa do Jacaré Formation, Bambuí Foreland Basin (Ediacaran-Cambrian), Southeast Brazil - Santana Dantas, Márcio Vinicius; Uhlein, Alexandre; Uhlein, Gabriel Jubé; Okubo, Juliana [UNESP]; Moura, Samuel Amaral (Elsevier, 2023)
The Bambuí Group is a lithostratigraphic unit that comprises a mixed carbonate-siliciclastic platform deposited in a foreland basin. It is a 1st order sequence that filled the São Francisco Basin during the Ediacaran-Cambrian in southeast Brazil. The Lagoa do Jacaré Formation is the second carbonate unit of the Bambuí Group and is related to a 2nd-order regressive hemicycle composed of dark gray shallow water carbonates with high positive ẟ1³C values (>+10‰) related to the upper part of the Middle Bambuí Excursion (MIBE). We described four outcrops in the center-north of Minas Gerais state (Paraopeba, Curvelo, Montes Claros and Ubaí areas) coupled with ẟ13C and ẟ18O, and SEM-EDS analysis in order to support detailed facies analyses. One seismic line and three well logs in the south part of the Januária High were also used to define the stratigraphic framework of the Lagoa do Jacaré Formation in the Bambuí Foreland Basin system. Eight facies were interpreted from the outcrop data and grouped into five facies associations, that represent peritidal zone (FA1), ooidal sand shoals (FA5), tempestites of mid ramp (FA3), fine-grained carbonate of outer ramp (FA4), and fine-grained siliciclastic from offshore (FA2). The strong presence of terrigenous material (quartz, feldspars, muscovite, biotite, apatite) with some authigenic/diagenetic minerals (pyrite, titanite, rutile) in all facies are the main petrographic aspect of the studied carbonate rocks, related to high sedimentary input and some events during early diagenesis. FA1 with lower mean values of ẟ1³C (+9‰) predominates in the north, meanwhile FA3 is the main association in the south with higher ẟ1³C mean values (+12‰). This difference is probably related to the stratigraphic differences between the basal section (at south) and upper section (at north) of the Lagoa do Jacaré Formation. The Januária High was the main controlling element for the deposition of the carbonate ramp in the north sector of the basin, close to the Ubaí and Montes Claros cities. Probably, this structural high also played an important role as source area in the forebulge sector, uplifted by flexure due to the orogeny of the Brasília and Araçuaí (still in development) Belts (∼540-520 Ma). To the east, a N–S carbonate ramp system was developed in the back-bulge sector according to the main paleocurrents measurements. This ramp is related to a 300 m thickness section of the Lagoa do Jacaré Formation that was firstly identified and correlated to the successions on the surface using well logs, possibly registering at the top the decreasing in the ẟ1³C values, after the main stages of the MIBE probably in close association with Ediacaran-Cambrian boundary, related to the assembling of the Gondwana Supercontinent recorded in this region of southeast Brazil.
Keywords: Bambuí group; Ediacaran-cambrian carbonate; Facies analysis; Foreland basin